Using Evaluation to Ensure Quality Professional Development in Rural Schools - Katherine Mitchem; Deborah Wells; John Wells (Journal of Research in Rural Education, 2003)
Professional development practices implemented in ruralschoolsystems have often led nowhere. These practices seem to produce adult learning activities with few results other than participants 'mounting frustration and anot her innovation left by the wayside. To encourage the development ofproductive professional development, many studies are beginning to indicate the importance ofmaking evaluation central to the design ofprofessional development. Employing WI evaluative approach may assist staff developers in addressing the frequent criticism that professional development activities are disconnected from one another and do not/arm part ofa coherent program ofteacherlearning and development. The CIPP Model wasformulated by Stufflebeam (1966) to show how evaluation contributes to the decision-making process in program management, If't·propose a similar conceptual model for ongoing data-based professional development ill rural settings. This model provides practitioner with a useful and manageable toolfor incorporating all evaluative approach to the design. development, and deli very ofprofessional development. In addition we provide a practical application ofthe model to an ongoing rural professional development project.